IFNG +874A/T Polymorphism Among Asymptomatic HTLV-1-Infected Individuals Is Potentially Related to a Worse Prognosis - Queiroz, Maria A. F.; Azevedo, Vânia N.; Amoras, Ednelza da S. G.; Moura, Tuane C. F.; Guimarães Ishak, Marluísa de O.; Ishak, Ricardo; Vallinoto, Antonio C. R.; Martins Feitosa, Rosimar N. (Frontiers in Microbiology, 2018)
HTLV-1 infections are persistent and frequently latent, but productive infections trigger different mechanisms of immunological responses in which cytokine are important for the control of infection. The present study investigated the role of IFNG +874A/T polymorphisms among 153 HTLV-1 infected persons (33 persons clinically diagnosed as TSP/HAM, 22 with rheumatologic manifestations, 2 with dermatitis, 1 with uveitis, 95 asymptomatics) and 300 healthy control individuals. Genotyping and proviral load of HTLV-1 were performed using a real time PCR assay and the plasma level of IFN-γ was measured using an enzyme immunoassay (ELISA). Genotype frequencies were not significantly different, but the presence of allele T was higher (p<0.0142) among the asymptomatic persons. Plasma levels of IFN-γ were significantly higher (p<0.0137) among those with genotype TT. Their proviral load was also higher but showed no statistical significance. There was no difference in the plasma levels of IFN-γ among the symptomatic patients, even when ranked according to the disease presentation (TSP/HAM or rheumatologic manifestations). However, the difference among those asymptomatic with the allele T was significantly higher (p<0.0016) and similar to the plasma levels observed among symptomatic persons. The results suggest that the polymorphism of IFNG +874A/T may modulate the plasma levels of IFN-γ during HTLV-1 infection. Asymptomatic carriers of the polymorphic genotypes apparently develop the inflammatory response in a shorter time triggering the progression to HTLV-1 related diseases. The results suggests that HTLV-1 infected asymptomatic persons carrying IFNG +874A/T polymorphism should be followed closer in order to foresee the upsurge of clinical symptoms as they are potentially at risk to develop a worst prognosis of disease and should be the priority to start early available treatment procedures.